Corticosteroid-induced manic and/or psychotic symptoms: a systematic review - Gostoli, Sara; Carrozzino, Danilo; Raimondi, Giulia; Subach, Regina; Gigante, Graziano; Rafanelli, Chiara (Frontiers in Pharmacology, 2025)
IntroductionGiven their immunosuppressive and anti-inflammatory properties, corticosteroids are widely used. However, corticosteroid-induced psychiatric effects are deeply concerning, since they can be severe and require accurate differential diagnosis from primary psychiatric disorders. Among corticosteroid-induced psychiatric symptoms, what kind of patients under corticosteroids develop manic and/or psychotic symptoms and which risk factors are associated with their development remain unclear.MethodsThe present systematic review aimed at giving a comprehensive overview of corticosteroids-induced symptoms of mania and/or psychosis and at examining the clinical factors that might increase the risk of developing these adverse reactions. According to PRISMA guidelines, this systematic review included 40 papers (clinical cases = 34; quantitative research = 6).ResultsIn 64.7% of clinical cases and 33.3% of research studies reviewed, patients taking corticosteroids presented with both manic and psychotic symptoms; in 11.8% of clinical cases and 1 (out of 6) quantitative research patients under corticosteroids presented with manic symptoms only, whereas in 23.5% of clinical cases and 3 quantitative studies, psychotic symptoms only. Prolonged and high-dose corticosteroid therapy, pre-existing psychiatric conditions, older age and female sex represent risk factors, which are likely to increase individual susceptibility to corticosteroid-induced symptoms of mania and/or psychosis.DiscussionAlthough manic and psychotic symptoms often coexist in patients taking corticosteroids, the direction and nature of this relationship (e.g., which symptoms appear first, their interaction and progression over time) remain unclear. Clinicians prescribing corticosteroids might take advantage of clinimetric methods, which may allow a substantial improvement in the early detection and evaluation of severity of corticosteroid-induced manic and/or psychotic symptoms.